Proceedings of IEEE Computer Society Conference on Computer Vision and Pattern Recognition
DOI: 10.1109/cvpr.1997.609309
|View full text |Cite
|
Sign up to set email alerts
|

LAFTER: lips and face real time tracker

Abstract: This paper describes an active-camera real-time system for tracking, shape description, and classification of the human face and mouth using only an SGI Indy computel:The system is based on use of 2 -0 blob features, which are spatially-compact clusters of pixels that are similar in terms of low-level image properties. Patterns of behavior (e.g., facial expressions and head movements) can be classified in real-time using Hidden Markov Model (HMM) methods. The system has been tested on hundreds of users and has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
86
0
1

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(87 citation statements)
references
References 24 publications
0
86
0
1
Order By: Relevance
“…Hidden Markov Models (HMMs) [16] and extensions have been one of the most popular modeling techniques. Some of the earliest work was done by Starner and Pentland in [18] where they used HMMs for recognizing hand movements in American Sign Language and by Oliver et al [12] to recognize facial expressions. More complex models, such as Parameterized-HMMs [19], Entropic-HMMs [1], Variable-length HMMs [7], Coupled-HMMs [2], structured HMMs [17] and context-free grammars [8] have been used to recognize more complex activities such as the interaction between two people.…”
Section: Prior Related Work On Human Activity Recognitionmentioning
confidence: 99%
“…Hidden Markov Models (HMMs) [16] and extensions have been one of the most popular modeling techniques. Some of the earliest work was done by Starner and Pentland in [18] where they used HMMs for recognizing hand movements in American Sign Language and by Oliver et al [12] to recognize facial expressions. More complex models, such as Parameterized-HMMs [19], Entropic-HMMs [1], Variable-length HMMs [7], Coupled-HMMs [2], structured HMMs [17] and context-free grammars [8] have been used to recognize more complex activities such as the interaction between two people.…”
Section: Prior Related Work On Human Activity Recognitionmentioning
confidence: 99%
“…A number of different color spaces have been used; however, normalized RGB [7,12,20,31] and HSV [8,14,22,24] are the most common color spaces used. It has been shown that in addition to being tolerant to minor variations in the illuminant, these color spaces also tend to produce minimum overlap between skin-color and background-color distributions [23].…”
Section: Related Workmentioning
confidence: 99%
“…Statistical approaches can be subdivided further into: parametric approaches [4,5,7,8,12,22,24,25] and non-parametric approaches [1,14,20,31].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations